Antimicrobial activity of the synthetic peptide Lys-a1 against oral streptococci - Da Silva, Bruno Rocha; De Freitas, Victor Aragão Abreu; Carneiro, Victor Alves; Arruda, Francisco Vassiliepe Sousa; Lorenzón, Esteban Nicolás [UNESP]; De Aguiar, Andréa Silvia Walter; Cilli, Eduardo Maffud [UNESP]; Cavada, Benildo Sousa; Teixeira, Edson Holanda (Elsevier, 2013)
The peptide LYS-[TRP6]-Hy-A1 (Lys-a1) is a synthetic derivative of the peptide Hy-A1, initially isolated from the frog species Hypsiboas albopunctatus. According to previous research, it is a molecule with broad antimicrobial activity. The objective of this study was to evaluate the antimicrobial activity of the synthetic peptide Lys-a1 (KIFGAIWPLALGALKNLIK- NH2) on the planktonic and biofilm growth of oral bacteria. The methods used to evaluate antimicrobial activity include the following: determination of the minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) in microtiter plates for growth in suspension and quantification of biomass by crystal violet staining and counting of colony forming units for biofilm growth. The microorganisms Streptococcus oralis, Streptococcus sanguinis, Streptococcus parasanguinis, Streptococcus salivarius, Streptococcus mutans and Streptococcus sobrinus were grown in Brain Heart Infusion broth at 37 °C under atmospheric pressure with 10% CO2. The peptide was solubilized in 0.1% acetic acid (v/v) at various concentrations (500-1.9 μg mL-1). Chlorhexidine gluconate 0.12% was used as the positive control, and BHI culture medium was used as the negative control. The tested peptide demonstrated a remarkable antimicrobial effect, inhibiting the planktonic and biofilm growth of all strains tested, even at low concentrations. Thus, the peptide Lys-a1 is an important source for potential antimicrobial agents, especially for the control and prevention of microbial biofilms, which is one of the most important factors in cariogenic processes. © 2012 Elsevier Inc.
Keywords: Antimicrobial peptide; Biofilms; Dental caries; Streptococcus mutans; acetic acid; chlorhexidine gluconate; crystal violet; polypeptide antibiotic agent; synthetic peptide Lys a1; unclassified drug; antibacterial activity; atmospheric pressure; bacterial growth; bacterium colony; biofilm; controlled study; drug solubility; growth inhibition; microtiter plate assay; minimum bactericidal concentration; minimum inhibitory concentration; nonhuman; plankton; priority journal; Streptococcus; Streptococcus oralis; Streptococcus parasanguinis; Streptococcus salivarius; Streptococcus sanguinis; Streptococcus sobrinus; Anura; Bacteria (microorganisms)